Inhibition of Bacillus cereus strains by antimicrobial metabolites from Lactobacillus johnsonii CRL1647 and Enterococcus faecium SM21 - Soria, María Cecilia (2014)
Bacillus cereus is an endospore-forming, Gram-positive bacterium able to cause food-borne diseases. Lactic acid bacteria are known for their ability to synthesize organic acids and bacteriocins, but the potential of these compounds against B. cereus has been scarcely documented in food models. The present study has examined the effect of the metabolites produced by Lactobacillus johnsonii CRL1647 and Enterococcus faecium SM21 on the viability of select B. cereus strains. Furthermore, the effect of E. faecium SM21 metabolites against B. cereus strains has also been investigated on a rice-food model. L. johnsonii CRL1647 produced 128 mmol/L of lactic acid, 38 mmol/L of acetic acid and 0.3 mmol/L of phenyl-lactic acid. These organic acids reduced the number of vegetative cells and spores of the B. cereus strains tested. However, the antagonistic effect disappeared at pH 6.5. On the other hand, E. faecium SM21 produced only lactic and acetic acid (24.5 and 12.2 mmol/L, respectively) and was able to inhibit both vegetative cells and spores of the B. cereus strains, at a final fermentation pH of 5.0 and at pH 6.5. This would indicate the action of other metabolites, different from organic acids, present in the cell-free supernatant. On cooked rice grains, the E. faecium SM21 bacteriocin(s) were tested against two B. cereus strains. Both of them were significantly affected within the first 4 h of contact; whereas B. cereus BAC1 cells recovered after 24 h, the effect on B. cereus 1 remained up to the end of the assay. The lactic acid bacteria studied may thus be considered to define future strategies for biological control of B. cereus.